2023
DOI: 10.3390/nu15061372
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High Protein Diets on Cardiovascular Outcomes: A Systematic Review and Meta-Analysis of Prospective Cohort Studies

Abstract: High protein diets have gained increased popularity as a means of losing weight, increasing muscle mass and strength, and improving cardiometabolic parameters. Only a few meta-analyses have addressed their impact on cardiovascular morbidity and mortality and failed to show any significant associations without applying strict values to define high protein intake. Due to the conflicting research background, we conducted a meta-analysis to assess the impact of high protein diets compared to normal protein consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…The most recent systematic review and meta-analysis of prospective cohort studies (fourteen studies, healthy participants, n 656 490) by Mantzouranis et al (22) found no relationship on total protein for cardiovascular death, stroke or a composite endpoint of stroke, nonfatal myocardial infarction and cardiovascular death, but did not investigate differences between animal and plant proteins. Part of the rationale for this study was that previous meta-analyses used a vague definition of high(er) protein diets, where they split the sample population by percentiles and compared highest with lowest protein intakes.…”
Section: High-protein Diets Cvd and All-cause Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent systematic review and meta-analysis of prospective cohort studies (fourteen studies, healthy participants, n 656 490) by Mantzouranis et al (22) found no relationship on total protein for cardiovascular death, stroke or a composite endpoint of stroke, nonfatal myocardial infarction and cardiovascular death, but did not investigate differences between animal and plant proteins. Part of the rationale for this study was that previous meta-analyses used a vague definition of high(er) protein diets, where they split the sample population by percentiles and compared highest with lowest protein intakes.…”
Section: High-protein Diets Cvd and All-cause Mortalitymentioning
confidence: 99%
“…Part of the rationale for this study was that previous meta-analyses used a vague definition of high(er) protein diets, where they split the sample population by percentiles and compared highest with lowest protein intakes. Pointing this out as a limitation that even the highest intake may still be within normal range intakes, Mantzouranis et al (22) created an arbitrary cut-off of 18 % EI, equivalent to approximately 1⋅3-1⋅4 g/kg/d protein intake, based on previous definitions of HPD falling between 1⋅2 and 1⋅6 g/kg/d. The meta-analysis included thirteen studies (n 656 490), the HPD group consumed 92⋅5 g/d of protein daily, and 72⋅8 g/d in the SPD groupless than the aforementioned 1⋅4 g/kg/d cut-off for average male and female weight of 85 and 72 kg respectively and more like a combined 1⋅2 g/kg/d although still higher than the global 0⋅8 g/kg/d.…”
Section: High-protein Diets Cvd and All-cause Mortalitymentioning
confidence: 99%